Expenditure Cuts and Access to Healthcare Under the Great Recession in Europe: Income Groups Are Unequally Affected - Torfs, Lore; Adriaenssens, Stef; Lagaert, Susan; Sara, Willems (International Journal for Equity in Health, 2021)
Background: The Great Recession, starting in 2008, was characterized by an overall reduction in living standards. This pushed several governments across Europe to restrict expenditures, also in the area of healthcare. These austerity measures are known to have affected access to healthcare, probably unevenly among social groups. This study examines the unequal effects of retrenchment in healthcare expenditures on access to medical care for different income groups across European countries. Method: Using data of two waves (2008 and 2014) of the European Union Statistics of Income and Living Conditions survey (EU-SILC), a difference-in-differences (DD) approach was used to analyse the overall change in unmet medical needs over time within and between countries. By adding another interaction, the differences in the effects between income quintiles (difference-in-difference-in-differences: DDD) were estimated. To do so, comparisons between two pairs of a treatment and a control case were made: Iceland versus Sweden, and Ireland versus the United Kingdom. These comparisons are made between countries with recessions equal in magnitude, but with different levels of healthcare cuts. This strategy allows isolating the effect of cuts, net of the severity of the recession. Results: The DD-estimates show a higher increase of unmet medical needs during the Great Recession in the treatment cases (Iceland vs. Sweden: + 3.24 pp.; Ireland vs. the United Kingdom: + 1.15 pp). The DDD-estimates show different results over the two models. In Iceland, the lowest income groups had a higher increase in unmet medical needs. This was not the case in Ireland, where middle-class groups saw their access to healthcare deteriorate more. Conclusion: Restrictions on health expenditures during the Great Recession caused an increase in self-reported unmet medical needs. The burden of these effects is not equally distributed; in some cases, the lower-income groups suffer most. The case of Ireland, nevertheless, shows that certain policy measures ...